Diseño e implementación de una máquina para la siembra de quinua - Gaibor Velasco, Alvaro Eduardo (2018)
Quinoa (Chenopodium quinoa willd) is a cereal that for its nutritional benefits, in the last times, has increased its cultivation. Additionally, there is evidence that it was the basic food for the populations that lived in the great part of America, before the arrival of the Spaniards. The preference, today, for nutritious and organic foods has promoted the recognition and valuation of quinoa, giving an important thrust its cultivation from the Faculty of Agricultural Sciences and Natural Resources (Caren) at the Technical University of Cotopaxi as well as from government agencies, MAGAP. The aim of the research study is the construction of a quinoa seeding machine in order to facilitate the work of sowing in the Faculty of Agricultural Sciences and Natural Resources (Caren) and to support the research innovations in the agricultural field. The methodology developed for the construction of the seeding machine was based on experimentation, a method wherein one or more independent variables can be manipulated to validate the effectiveness of the proposed machine. The time, speed and weight that the machine has in the motion of sowing the cereal on the ground will be measured to obtain the qualities and properties of the assembled machine. The seeding machine has the height recommended by the farmers of the sector, 1.70 meters. The accessories for movement and dosage are mainly composed of a pinion, chain and bearings, which give versatility in the field at the time of sowing with an appropriate mechanism that allows the operator to accelerate according to their need. The quinoa seeding machine is a tool, which may help not only to reduce the costs when sowing the cereal but also to motivate the farmers in their planting, both for consumption and to advertise the product.